A realistic description of influence of the magnetic field strength on high gradient magnetic separation. (August 2015) - Zheng, Xiayu; Wang, Yuhua; Lu, Dongfang
Highlights: The particle buildup profile increase with the increase of magnetic field. Low grade intergrowths largely accumulate on matrices in high magnetic field. Competitive accumulation between the mineral intergrowths and monomers. Coarse intergrowths can accumulate on the matrices precede the fine monomers. Approaches to obtain a product of high grade and recovery. Abstract: The magnetic field strength is a very important parameter in high gradient magnetic separation (HGMS). It was usually thought that the increase of magnetic field strength will lead to the decrease of the minerals' susceptibility and the matrices' surface area available for the buildup of the magnetic particles, which was responsible for the decrease of the mineral recovery in high magnetic field. But the detailed influence of the magnetic field strength on the behavior of the particles of different characteristics in HGMS is still not clear. A very important factor was usually ignored in the process of HGMS, namely the behavior of the low grade intergrowths. In this article, the influence of magnetic field strength on the behavior of the magnetic monomers and intergrowths in HGMS was investigated with the particle buildup model and the particle capture model. The buildup profile of the magnetic monomers increases with the increase of the magnetic field strength despite the decrease of the minerals' susceptibility. The low grade intergrowths can hardly accumulate on the matrices in a low magnetic field but can largely accumulate on the matrices in a high magnetic field. In a high magnetic field, there exists the competitive accumulation between the low grade intergrowths and the fine monomers. Coarse intergrowths may have larger buildup profile and shorter capture time than the fine monomers and will accumulate preferentially on the matrices. In some circumstances, the competitive accumulation of the particles will lead to the decrease of the recovery in a high magnetic field. A moderate high magnetic field can ensure a high recovery. For a magnetic product of high grade and recovery, high monomer dissociation degree is necessary and the over grinding of the minerals should be avoided, and classifying the minerals to handle the coarse fraction and the fine fraction separately can also be considered.